Fear of racism, employment and expected organizational racism: their association with health - Bécares, Laia (European journal of public health, 2009)
Background: Racism has been argued to be a focal element of larger societal inequalities which generate ethnic health disparities. Despite suggestions that socio-demographic characteristics of the victim may influence the impact of racism on health, little is known in the United Kingdom about how self-reported experiences of racism vary by socio-demographic characteristics, whether racism contributes to ethnic differences in health and whether there is a differential association between racism and health for certain socio-demographic groups. Methods: Multilevel logistic regression models were conducted using data from the 2005 Citizenship Survey to identify the demographic characteristics associated with reporting experienced racism; explore the association between health, racism and its contribution to ethnic inequalities in health; and explore the moderating role that gender, age, ethnicity and socio-economic position (SEP) have in the relationship between racism and health. Results: Females were significantly more likely to report fear of racial and religious attacks, but reported lower odds of experiencing employment and expected organizational discrimination. A trend was observed for decreasing employment discrimination as SEP decreased. A reverse association was found for SEP and expected organizational discrimination, where people in the lowest employment categories reported lower odds of experiencing discrimination. Conclusion: This study highlights variations in the types of racial discrimination most commonly reported across different socio-demographic characteristics. Despite substantial differences in the experience of racial discrimination, the detrimental impact of racism on health was the same across socio-demographic groups.